PERBEDAAN KEMAMPUAN BERBICARA ANAK YANG DIASUH ORANG TUA SENDIRI DAN YANG DIASUH OLEH PENGASUH (STUDI KASUS PADA 2 ANAK TETANGGA) - yuli astrina sari (incrementapedia, 2019)
This research is motivated by differences in parenting that can affect the development of children aged 2-3 years, especially in terms of the ability to speak. Based on observations made with regard to language and talk of children, are still limited in pronunciation and speech fluency. Through speaking, the child can communicate, convey thoughts, ideas and feelings so that children are able to interact and build relationships social surroundings. Therefore, the need for stimulation that can increase the child's ability to speak, one of them through the method of conversing. The purpose of this study was to describe the differences in the ability to speak of the children within their own and with cared for by a caregiver. This is a qualitative research with a case study approach. The technique used an expose facto. Expose facto selected, because the cases studied individual. The results indicate differences in the ability to speak between children raised by their own parents and those cared for by caregivers. The children raised by caregivers show a better development of speech skills than children raised by their own parents.